(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The use of computer simulation methods in the study of complex systems in almost all areas of science and technology is a prerequisite. Here, with the help of modern powerful computational methods, one can deeply, in detail and visually study an object (phenomenon, process). In this article, using regression analysis, a mathematical model has been developed that describes the dependence of the heat of combustion of coal on its thermophysical parameters. When modeling, the results of studies conducted by scientists on 7 types of coals in Kyrgyzstan were used. The regression parameters were estimated using the least squares method. The developed regression model was tested for accuracy and quality, and the statistical significance of the regression equation and its coefficients were evaluated using Fisher and Student’s criteria. The results of the experimental method were confirmed on a computer model created in the MathCAD system. As a result, with the help of the created computer model, it was possible to determine the quality of coal and make a forecast for improving its quality.